Julian Barnes - Childs, Peter, 1962- (Contemporary British novelists., 2011)
This is a comprehensive introductory overview of Julian Barnes's novels that situates his work in terms of fabulation and memory, irony and comedy. It pursues a broadly chronological line through Barnes's literary career, but along the way it also shows how certain key thematic preoccupations and obsessions seem to tie Barnes's oeuvre together (love, death, art, history, truth, and memory).